Control of Gray Mold on Tomato plants by Spraying Piper nigrum and Urtica dioica Extracts under Greenhouse Condition - Ghazal, Hamed N.; Al-Shahwany, Ayyad W; Al–Dulaimy, Firas T. (Iraqi Journal of Science, 2019)
Field experimented were examined the effects of Piper nigrum and Urtica dioica extracts on the gray mold disease in tomato that caused by Botrytis cinerea. To evaluate the inducing resistance of these extracts, many treatments were sprayed on tomato leaves, including methanolic and aquatic extracts, Silver nano particles biosynthesis (AgNPs) and water as (control).The results indicated that the resistance of tomato plants was increased when tomato plant sprayed first with Methanolic P. nigrum extracts and after 4 hours sprayed with B. cinerea. Also, spraying with methanolic and aquatic AgNPs P. nigrum extract were reduced gray mold disease. These results were showed that P. nigrum AgNPs treatment reduced the gray mold of tomato leaves because of the activities of total phenolic compounds which was infected with Botrytis cinerea.